Iranian Nurses’ Perception of Factors Contributing to Medical Errors in Intensive Care Unit: A Qualitative Study - Tahereh Najafi Ghezeljeh; Mansoureh Ashghali Farahani; Fatemeh Kafami Ladani (Acta Medica Iranica, 2022)
Patient safety is a major health concern throughout the world, and medical errors are the most important factor threatening patient safety, especially in the Intensive Care Unit (ICU). To prevent errors and improve patient safety, it is necessary to identify the underlying causes of error from the perspective of nurses working in ICUs. This study aimed to explore nurses’ experiences of factors contributing to medical errors in the Intensive Care Unit. The present qualitative study was conducted using conventional content analysis. The participants included 17 nurses working in ICUs in two educational hospitals affiliated with the Iran University of Medical Sciences in Tehran. Data were collected using in-depth semi-structured interviews and were analyzed through the conventional content analysis approach based on Graneheim and Lundman's model. Four main categories (a) extra-organizational challenges; (b) Organizational position; (c) The specificity of the care environment, (d) Individual reason and nine subcategories: (accreditation problems, non-native care standards, organizational management, organizational Features, critical condition of patients, physical structure of unit, neglect in the process of care, lack of clinical knowledge and experience, and physical and psychological problems) were identified. From the nurses' perspective, a series of factors associated with the health system, the organization, the ICUs, and the individual play a role in the occurrence of errors; therefore, it is necessary for planners, policy-makers, nursing managers to think about these underlying factors and with in-service training, and a positive, supportive atmosphere; lead nurses to support the patient and improve patient safety.